A Short Review on Circulating Micro-RNAs in Diabetic Patients - Michele, Carella Angelo; Teresa, Marinelli; Armando, Melfitano; Michele, Di Pumpo; Giovanni, Modola; Pasquale, De Luca; Angelo, Benvenuto (Highlights on Medicine and Medical Science Vol. 15, 2021)
microRNAs (miRNAs) are short noncoding RNA sequences, approximately 20-22 nucleotides, synthesized in the cell nucleus, through a complex multi-step biosynthetic process, starting from RNA polymerase II. miRNAs regulate a wide range of biological processes as cell differentiation, proliferation and development, cell-to-cell communication, cell metabolism and apoptosis. There is evidence that miRNAs may have a role in molecular mechanisms linked to cellular pathways of certain diseases, as viral infections, cancer, diabetes and cardiovascular disease. miRNAs expression was investigated in diabetes mellitus: a lot of altered circulating levels of different miRNAs were found to be linked to type 1 and type 2 diabetes, both at onset and in advanced disease. At least 12 circulating miRNAs were found consistently dysregulated in type 1 diabetes mellitus and, more or less, 40 circulating miRNAs in type 2 diabetic patients. miR-126 seems to be miRNA most linked to pathways and development of type 1 and type 2 diabetes and their complications. Dysregulation of several miRNAs involves different aspects of diabetic disease: glycemic control, residual beta cell function, insulin secretion and sensitivity, micro- and macro-vascular complications, particularly endothelial dysfunction, renal disease and retinopathy. The analysis of circulating miRNAs might be a good source of diagnostic and prognostic biomarkers in diabetic patients. Large and long-term clinical studies should be conducted to evaluate the value of these nucleotides as biomarkers for predicting progression of diabetes, though the high detection costs might be the main limitations on their use in daily clinical practice.